Naringenin Attenuates Non-Alcoholic Fatty Liver Disease by Enhancing Energy Expenditure and Regulating Autophagy via AMPK - Yang, Ying; Wu, Yue; Zou, Jie; Wang, Yu-Hao; Xu, Meng-Xia; Huang, Wei; Yu, Dao-Jiang; Zhang, Li; Zhang, Yuan-Yuan; Sun, Xiao-Dong (Frontiers in Pharmacology, 2021)
Background: The prevalence of non-alcoholic fatty liver disease (NAFLD) keeps growing recently. Purpose: To investigate the effects and mechanisms of naringenin (NAR) on NAFLD. Methods: High-fat diet (HFD)-induced NAFLD rats were orally administered with NAR at 10, 30, and 90 mg/kg for two weeks. The serum level of triglyceride (TG), total cholesterol (TC), glutamic-oxaloacetic transaminase (AST), and glutamic-pyruvic transaminase (ALT) was measured. The hepatic histology was detected by H&E and oil red O staining. L02 and Huh-7 cells were induced by sodium oleate to establish a NAFLD cell model. The effects of NAR on lipid accumulation were detected by oil red O staining. The glucose uptake and ATP content of 3T3-L1 adipocytes and C2C12 myotubes were measured. The expression of proteins of the AMPK signaling pathway in 3T3-L1 adipocytes and C2C12 myotubes was assessed by Western blotting. The mitochondrial biogenesis of 3T3-L1 adipocytes and C2C12 myotubes was measured by mitotracker orange staining and Western blotting. The biomarkers of autophagy were detected by Western blotting and immunofluorescence. The binding of NAR to AMPKγ1 was analyzed by molecular docking. Chloroquine and compound C were employed to block autophagic flux and AMPK, respectively. Results: NAR alleviated HFD-induced NAFLD in rats at 10, 30, and 90 mg/kg. NAR attenuated lipid accumulation in L02 and Huh-7 cells at 0.7, 2.2, 6.7, and 20 μM. NAR increased glucose uptake, decreased the ATP content, activated the CaMKKβ/AMPK/ACC pathway, and enhanced the mitochondrial biogenesis in 3T3-L1 adipocytes and C2C12 myotubes. NAR increased autophagy and promoted the initiation of autophagic flux in 3T3-L1 preadipocytes and C2C12 myoblasts, while it inhibited autophagy in NAFLD rats, 3T3-L1 adipocytes, and C2C12 myotubes. Molecular docking showed that NAR binds to AMPKγ1. Compound C blocked effects of NAR on lipid accumulation and autophagy in L02 cells. Conclusion: NAR alleviates NAFLD by increasing energy expenditure and regulating autophagy via activating AMPK directly and indirectly. The direct binding of NAR and AMPKγ1 needs further validation.